The Development of Learning Achievement in General Knowledge about Bills of Exchange through the Poki Application among Second-Year Vocational Certificate Students - อ้วนแก้ว ศิรินันท์; พิพัฒนภูมิพร นรภัทร; แย้มชุติ นภวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed: 1) to compare the learning achievement in the general knowledge about bills of exchange before and after using games from Poki application for learning and 2) examine students’ acceptance of the Poki application for learning in accounting about bills of exchange. The sample group consisted of 45 second-year vocational certificate students selected through cluster random sampling. The research instruments included: 1) the lesson plan utilizing games from the Poki application, 2) the learning achievement test, and 3) the questionnaire on students’ opinions. The statistical methods used for data analysis included mean, standard deviation, and a dependent t-test. The research findings revealed that: 1) the students who learned by using games from the Poki application had significantly higher post-learning achievement ( Mean = 13.71, S.D. = 4.01) compared to their pre-learning achievement (Mean = 7.51, S.D. = 2.81) at a significance level of 0.05 and 2) the students strongly agreed with the acceptance of the Poki application in learning in accounting about bills of exchange, with the overall rating at the highest level ( Mean = 4.53, S.D. = 0.61).